Longitudinal associations between psychological factors, community integration, and suicide risks among patients with treatment-resistant depression in Vietnam - Huong, Pham Thi Thu; Wu, Chia-Yi; Been, Lee Ming; Van Tuan, Nguyen; Hien, Pham Thi Thu; Lan Anh, Nguyen Thi; Son, Nguyen Thi; Hien, Nguyen Thi Thu (Frontiers in Psychiatry, 2025)
ObjectiveTo examine longitudinal associations of psychological distress, community integration, suicide ideation, and attempts within 3-month post-discharge period among patients with treatment-resistant depression (TRD).MethodsProspective study design with a 3-month followed-up from the hospital admission through community reintegration. All the 53 patients with TRD were interviewed one week after admission (T0) plus 1-month (T1) and three months (T2) after discharge with a structured questionnaire from October 2021 to September 2022. Descriptive and correlational analysis of the trend and associates of TRD suicide risks were performed.ResultsThe results revealed that suicide ideation and attempt rates reduced after inpatient treatment, but increased altogether from T1 to T2 in the community. Nearly half of the participants (46%) reported recent suicide ideation, and 13.46% attempted suicide at T2. Perceiving poor quality of life and a low level of community integration performance were associated modestly with suicide ideation, with 1.02- and 1.10-times higher risk, respectively. On the other hand, a high level of psychological distress increased the hazard of suicide attempts by 1.13-fold.ConclusionsOur findings suggest future suicide prevention strategies and the importance of regular assessment of inpatients and outpatients for psychological distress to identify and engage high-risk individuals.